Evaluation of Hospital Management Information System (SIMRS) Implementation in Radiology Services Using PIECES Framework at “Hospital X” Jakarta - Aurelia; Harahap, Sarah Geltri; Yari, Yarwin (LPPM Universitas Dhyana Pura, 2025)
The implementation of Hospital Management Information Systems (SIMRS) is crucial in enhancing efficiency, security, and the overall quality of radiology services. However, the integration between Radiology Information System (RIS), Picture Archiving and Communication System (PACS), and Electronic Medical Records (EMR), particularly through standards such as HL7 and DICOM remains a challenge in many hospitals, including “Hospital X” Jakarta. This study aims to evaluate the implementation of SIMRS in the radiology department using the PIECES framework (Performance, Information & Data, Economy, Control & Security, Efficiency, and Service). A qualitative case study approach was applied, with data collected through in-depth interviews involving 15 informants from different professional categories within the radiology unit. Thematic analysis was conducted with coding guided by the PIECES framework. Findings reveal that SIMRS supports improvements in Information & Data management, operational Economy, and Control & Security, particularly in reducing paper-based processes and improving access to digital records. Nevertheless, issues persist in Performance, Efficiency, and Service, such as frequent network latency, duplication in EMR entries, and limited accessibility of PACS outside designated terminals. Based on these results, it is recommended that “Hospital X” not only conduct regular monitoring of hardware capacity and network stability, but also adopt strategic measures, including policy development toward filmless radiology, strengthening interoperability across RIS–PACS–EMR systems, and implementing more rigorous data security audits.